Theater as a Tool in Promoting Positive Discipline for Children a Case Study - Blanco, Felimon Bonita (Talas, 2023)
The study aims to present a qualitative inquiry on using theater as a tool in educating communities on positive discipline for children. It investigates the impact of the advocacy play Istoryahe Lang Ko on the parents and family heads in relation to positive discipline for children. This is a case study that uses the Social Learning Theory of Albert Bandura as the main framework of the inquiry. Participants of the study were ten parents from the City of Ozamiz who watched the play that was staged in their barangay. The study revealed that the use of theater is an effective tool in conveying messages and issues to the community. It also revealed that communities prefer theater over traditional lecture as method in educational activities. The results of the study showed that staging plays in the communities leave an impact on parents and family heads in relation to positive discipline for children. This study concludes that theater, being a live art, easily connects with the audience; thus, learning of the message easier and clearer. The play changes perspectives among parents in relation to corporal punishment and positive discipline for children.